Single-cell and genetic multi-omics analysis combined with experiments confirmed the signature and potential targets of cuproptosis in hepatocellular carcinoma - Cao, Feng; Qi, Yong; Wu, Wenyong; Li, Xutong; Yang, Chuang (Frontiers in Cell and Developmental Biology, 2023)
Cuproptosis, as a recently discovered type of programmed cell death, occupies a very important role in hepatocellular carcinoma (HCC). However, the functions of cuproptosis in HCC are still unclear. In this study, we first analyzed the transcriptome data and clinical information of 526 HCC patients using multiple algorithms and extensively described the copy number variation, prognostic and immune infiltration characteristics of cuproptosis related genes (CRGs). Then, we screened 5 hub genes associated with prognosis through LASSO and Cox regression analyses and constructed a prognostic prediction model. Then, we further explored the key gene biological function by single-cell analysis, cell viability and transwell experiments. Meantime, we also analysed the molecular docking of the hub genes. And the results showed that patients in the high-risk group had poor prognosis and high expression levels of multiple immune markers. The molecular experiments and single-cell analysis results showed that BEX1 were higher expressed in HCC tissues and deletion inhibited the proliferation, invasion and migration and EMT pathway of HCC cells. Finally, it was observed that BEX1 could bind to sorafenib to form a stable conformation. Therefore, this study not only revealed the multiomics characteristics of CRGs in HCC, but also constructed a new high-accuracy prognostic prediction model. Meanwhile, BEX1 were also identified as hub genes that can mediate the cuproptosis of hepatocytes as potential therapeutic targets for HCC.